The Variables Predicting the Appointment of Candidate Teachers to Primary Schools - Nuri DOĞAN; Ali Ekber ŞAHİN (İnönü Üniversitesi Eğitim Fakültesi Dergisi)
The purpose of this study was to examine the variables that predict the appointment status of candidate teachers as a result of the Public Personnel Selection Test (PPST). In this study, an answer was searched for the question “Do certain demographic variables, PPST standard scores, University Student Selection Test scores, students’ achievement results in professional courses, and grade point average (GPA) of students have any effect on the appointment status of teacher candidates?” Since the dependent variable of this study was categorical (appointed, not appointed), logistics regression technique was used. In the regression model, some variables such as divisions of teacher candidates and GPA were found to be important predictors. The classification success level of variables included in the equation was found to be 72%. Based on these findings it is concluded that some of the variables taken into consideration in this study have an important effect on the appointment status of teacher candidates.